The acquisitive methods of reading and understanding of Chinese essays and problems of extracting meanings of Chinese characters - Wong, Ling Yan (2011)
This paper investigate the methods adopted by non-Chinese learners to extract the meanings of Chinese characters in reading Chinese essays. All the respondents are selected to be involved in this study are Malay students from Universiti Putra Malaysia who learned Chinese language as a foreign language. This study will identify mother tongue of the respondents will bring or cause some problems to non-Chinese learners in reading and understanding the Chinese essays, and the objective of this survey is to investigate reading method which adopted by the respondents in understanding Chinese essays whether the respondent directly extract meanings from written forms of Chinese characters or they need to transit from an intermediate step where the respondents will transfer written forms of Chinese characters into sound segments, and they will extract meanings of Chines characters from its sound segments. This study has revealed two main findings. Firstly, cognitive thinking of the respondents is interrupted by their mother tongue interferences, in the process of reading and understanding Chinese essays, they need to pass through the intermediate step which is transfering written forms of Chines characters to sound segments, and they adopted the sound system of their mother tongues to spell the prnunciation of Chinese characters in Chinese essays. Secondly, the respondents were interfered by acquisitive method of interlanguage, although they tried to extricate themselves from mother tongue interference, and adopted letters of the Chinese standard pronunciation to spell pronunciation of Chinese characters which appeared in essays, but in the reading process, the respondents also need to pass through the intermediate steps which mentioned early in order to extract meanings of Chinese characters for understanding the whole content of the essay. The sound segments of pronunciations under these two conditions are without tones, and the study found that this performance characteristics is one of the negative transfers from the respondents mother tongue interference. According to the findings of this research, the respondents are not completely unable distinguished four tone in the Chines sound system, they are actually able to master the level tone, the falling tone and the tortuous tone in Chinese sound system, but they felt difficulty to differentiate the rising tone and and the falling-rising tone, because these two tones are pronounced as a similarly tortuous tone. This paper is based on the character-based theory, interlanguage and cognitive theory as research theories and try to investigate the acquisitive methods which adopted by non-Chinese learners as the intermediate step to extract meanings of Chines characters in reading and understanding Chinese essays, and this study also identified the methods used by the respondents to transfer written forms of Chines characters to sound segments.